FISCAL AND MONETARY POLICIES IN LATIN AMERICAN COUNTRIES: A VAR PANEL APPROACH - Duarte, Leandro Batista; Santos, Raphael de Jesus; dos Santos Sobrinho, João Vitor; Belmiro, Maria Orlandia de Melo; Dantas, Geovane dos Reis; Freitas, Paloma Fernandes; de Jesus, Jamile da Silva Teixeira Goes; de Oliveira, Carlos Adrian Gomes; Santiago, Álefe Sampaio; Déo, Milena Andrade; de Lima, Edrei Santos; Santana, Valéria Caroline Batista (Seven Editora, 2026)
This article aims to evaluate the macroeconomic impact of fiscal policy and monetary policy shocks for Latin American countries, using the Vector Panel Auto-Regression (PVAR) model as methodology. In addition to trying to capture the effects of policies with a more complete model composed of 16 countries, the article also sought to present new results from a sub-sample as a form of robustness, controlling periods of instability, such as economic and financial crises and controlling by exchange rate regime floating.